PELATIHAN PEMBUATAN ECO-ENZIM UNTUK MENGURANGI LIMBAH RUMAH TANGGA DI KELURAHAN TANGKERANG LABUAI KOTA PEKANBARU - Susi Endrini; Siti Juariah; Isna Wardaniati; Wahyu Margi Sidoretno; Salsabila Marfyanda; Willy Octavia (Jurnal Hilirisasi IPTEKS, 2024)
Eco-enzyme is a versatile liquid that can be used in household, agriculture, livestock, and industrial fields. Its applications range from natural cosmetics, natural medicines, floor cleaners/disinfectants, insecticides, to liquid fertilizers that stimulate plant hormones to improve the quality of fruits and vegetables and increase harvest yields. Several methods of organic waste processing include eco-enzyme production and aerobic and anaerobic composting. Eco-enzymes are unique because they do not require extensive land for fermentation, unlike compost. This makes them very land-efficient and can be done at home. The purpose of this activity is to train housewives to reduce waste piles in the Tangkerang Labuai sub-district of Pekanbaru city by producing eco-enzyme products. The activity takes place in the Tangkerang Labuai sub-district. The target audience for this activity is housewives in the Tangkerang Labuai sub-district of Pekanbaru city. The method of this activity is training and evaluation. Training is conducted directly involving the target audience. Evaluation is done before and after training through pre-tests and post-tests. The results obtained are that housewives in the Tangkerang Labuai sub-district are skilled in producing eco-enzyme products, as evidenced by the results of eco-enzyme products that meet the quality criteria of eco-enzymes. The conclusion of this activity is that the implementation can proceed according to plan and it is hoped that the community can sustainably apply eco-enzyme production activities to reduce pollution in the environment of Pekanbaru city.